Design, Construction and Performance Evaluation of a Manually Operated Meat Mincing Machine - Kajiama, F. M.; Aji, M. A.; Shuwa, M.; Taktak, E. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In this study, a manually operated meat mincing machine was designed, constructed and its performance evaluated. The machine consists of; a single start worm auger called the shaft, a four-blade crosshead knife, a perforated plate, handle, mincing cover and a mincing head which comprised a hopper and an anchor bracket. All components of the machine were fabricated from locally available materials (stainless and mild steel) and based on the determined design parameters. The auger, mincing head, the crosshead knife and perforated plate were constructed from stainless steel material. Mild steel was used for the construction of the anchor bracket, mincing head cover and handle of the machine. These components were fabricated using the process of measurement, marking, cutting and joining. Vernier caliper and steel rule were used for measurement, scriber used for marking, center lathe machine, drilling machine, hark saw, hand snip and hand files were used for cutting. While arc welding and bolting were used the joining process. The auger had a shaft diameter of 0.025 m, worm diameter of 0.05 m and a total length of 0.22 m. The mincing head had an internal diameter of 0.052 m and external diameter of 0.06 m. The result shows that the machine can mince fresh meat in seconds, of perboiled meat in seconds and of overcooked meat in seconds. The critical load of the auger which is the major component of the machine is with a maximum stress of The efficiency of the machine was 50% at a velocity ratio of 0.88 and mechanical advantage of 1.8 with a total production cost of seven thousand three hundred and ninety two naira (₦7,392). The machine will serve as a means of providing minced meat to children, elderly and the sick especially in rural areas that have no access to electricity.